2019
DOI: 10.1111/1365-2745.13157
|View full text |Cite
|
Sign up to set email alerts
|

Domesticated tomatoes are more vulnerable to negative plant–soil feedbacks than their wild relatives

Abstract: Domesticated plants can differ from their wild counterparts in the strength and outcome of species interactions, both above‐ and belowground. Plant–soil feedbacks influence plant success, and plant‐associated soil microbial communities can influence plant interactions with herbivores and their natural enemies, yet, it remains unclear if domestication has changed these relationships. To determine the effects of domestication on plant–soil interactions, we characterized soil microbial communities associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 75 publications
5
34
0
Order By: Relevance
“…The lack of genetic correlation between resistance traits in our experimental set‐up goes in line with previous findings in wild tomatoes (e.g. Thaler & Karban, ; Koricheva et al , ), but also extends the observed pattern to later stages of the domestication of tomato (see also Carrillo et al , ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lack of genetic correlation between resistance traits in our experimental set‐up goes in line with previous findings in wild tomatoes (e.g. Thaler & Karban, ; Koricheva et al , ), but also extends the observed pattern to later stages of the domestication of tomato (see also Carrillo et al , ).…”
Section: Discussionsupporting
confidence: 92%
“…The lack of genetic correlation between resistance traits in our experimental set-up goes in line with previous findings in wild tomatoes (e.g. Thaler & Karban, 1997;Koricheva et al, 2004), but also extends the observed pattern to later stages of the domestication of tomato (see also Carrillo et al, 2019). Resistance to insect herbivory mediated by glandular trichomes is well represented in the genus Solanum, where four types of glandular trichomes (I, IV, VI, VII) and four nonglandular (II, III, V, VIII) have been described (Glas et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, whether these shifts in rhizosphere microbial communities can affect the outcome of plant soil feedbacks is less studied, with a few exceptions. For instance, Carrillo et al (2019) found that soils trained by domesticated tomatoes promote more negative feedbacks than its wild progenitors, and that was associated with shifts in the microbial biomass. Similarly, Miller & Menalled (2015) found negative feedbacks in plants growing in soils previously trained by crops, in comparison with plants growing in soils trained by wild species.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence showed that soils trained by domesticated tomatoes promoted more negative PSF than their relatives through shifts in microbial community composition (Carrillo et al, 2019). Although few case studies have provided useful insights, a broader analysis about the functional consequences of domestication on PSF in crops is missing.…”
Section: Introductionmentioning
confidence: 99%
“…Wild sunflower accessions are slightly more readily colonized by mycorrhizae (Turrini et al, 2016) and also less resistant to pathogens than domesticated lines (Leff et al, 2016). With regard to the crops studied here, previous studies have indicated that cultivated lettuce and maize plants assemble different microbiomes than their wild relatives (Cardinale et al, 2015;Szoboszlay et al, 2015), and that cultivated tomato plants respond differently to soil conditioning compared to their wild counterparts (Carrillo et al, 2019). It is also important to note that these studies found substantial cultivar-level variation in the microbiomes of these crop species, which emphasizes the need to not only characterize the responses of different plant species to microbiomes, but also a diverse range of genotypes within species.…”
Section: Discussionmentioning
confidence: 83%